South America - Streeter, Michael 1957- (Haus histories, 2010)
While Brazil declared war on Germany, in the First World War, the rest of South America held back. In the end no other South American nation joined the fighting. But four - Bolivia, Equador, Peru and Uruguay did break off diplomatic relations with Germany, in sympathy with US policy and with Allies in Europe. This title deals with this topic.